Fruiting efficiency : an alternative trait to further rise wheat yield - Slafer, Gustavo Ariel (2015)
Fil: Slafer, Gustavo Ariel. University of Lleida. Department of Crop and Forest Sciences and AGROTECNIO (Center for Research in Agrotechnology). Lleida, Spain.